SCHWANN AMS 12,018, Geistliche Gesänge der Mossi, Voltarepublik (Christian Songs of the Mossi). Sung by the Sisters of the Immaculate Conception, recorded at the Sisters’ monastery at Manga in 1960. A 7" 33? r.p.m. mono disc of good sound quality. Price DM 8,-. (International Library of African Music, 1968)
pages: 66
Keywords: African Music